2017
DOI: 10.1002/cne.24302
|View full text |Cite
|
Sign up to set email alerts
|

The reduction of intraepidermal P2X3 nerve fiber density correlates with behavioral hyperalgesia in a rat model of nerve injury‐induced pain

Abstract: Skin biopsies from patients with neuropathic pain often show changes in epidermal innervation, although it remains to be elucidated to what extent such changes can be linked to a particular subgroup of nerve fibers and how these changes are correlated with pain intensity. Here, we investigated to what extent behavioral signs of hyperalgesia are correlated with immunohistochemical changes of peptidergic and non-peptidergic epidermal nerve fibers in a rat model of nerve injury-induced pain. Rats subjected to uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 44 publications
(70 reference statements)
4
18
0
Order By: Relevance
“…In the peripheral terminals of sensory neurons, PLC-PKC cascade can directly activate or sensitize neighboring TRPV1 and TRPA1 channels in DRG [16,28,80,81]. According to the subdivision of DRG neurons, TRPV1-and TRPA1-positive neurons are related to both peptidergic and non-peptidergic nerve fibers, whereas P2 × 3-expressing neurons represent non-peptidergic DRG neurons [82][83][84][85][86][87]. It has been shown that the co-expression of other receptors with P2 × 3 in C-fibers can alter neuronal sensitization induced P2 × 3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…In the peripheral terminals of sensory neurons, PLC-PKC cascade can directly activate or sensitize neighboring TRPV1 and TRPA1 channels in DRG [16,28,80,81]. According to the subdivision of DRG neurons, TRPV1-and TRPA1-positive neurons are related to both peptidergic and non-peptidergic nerve fibers, whereas P2 × 3-expressing neurons represent non-peptidergic DRG neurons [82][83][84][85][86][87]. It has been shown that the co-expression of other receptors with P2 × 3 in C-fibers can alter neuronal sensitization induced P2 × 3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed immunohistochemical procedure is described in a recent publication. 36 In short, a two-step immunohistochemistry with Streptavidin-Biotin Complex was used for protein gene product 9.5 (PGP9.5), while additional tyramid signal amplification was applied for calcitonin gene-related peptide (CGRP). Concentrations of primary antibodies were 1:10,000 for rabbit anti-PGP 9.5 (Catalog# ADI-905–520; Enzo Life Sciences, Farmingdale, NY), 1:50,000 for guinea pig anti-CGRP (Catalog # 16013; Progen Biotechnik, Heidelberg, DE), and 1:100,000 for rabbit anti-CGRP (Catalog# PC205L; Millipore, Billerica, MA).…”
Section: Methodsmentioning
confidence: 99%
“…We also attempted to visualize the nonpeptidergic subclass of nociceptors in the skin, 36 using a histochemical staining method (i.e., acetylcholinesterase) 44 and various immunohistochemical markers (i.e., P2X 3 , IB4, RET, GINIP), 36 , 45 47 at varying concentrations and using specific protocols but were unable to obtain reproducible staining patterns allowing for quantification of these fibers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations